DAMPAK TINGKAT SUKU BUNGA KREDIT, INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP JUMLAH KREDIT BANK UMUM SWASTA NASIONAL YANG DISALURKAN DI INDONESIA - Muhammad Rizki Saputra; Ryan Juminta Anward; Rizali Rizali (Ecoplan, 2019)
The objective of this research is to (1) analyse the influence of loan interest rate, inflation and economic growth to loans disbursed by national private banks in Indonesia. This research uses quarterly data for ten years from 2007 to 2016. The methodology used in this research is time series econometric technique which is the unit root test, statistical test and classical assumption test. The result of this research shows that loan interest rate and inflation variable have a negative correlation and statistically is not significant to loans that disbursed by national private banks in Indonesia. While Indonesian economic growth and global economic variable have a positive correlation and statistically is significant to loans that disbursed by national private banks in Indonesia.